Plan de mejoramiento de la empresa Agro Comercio Torres García ubicada en la parroquia la Unión cantón Quinindé - Torres García, Catherine Gabriela (2016)
Agro Comercio Torres García is dedicated to the commercialization of cocoa and passion fruit in the parish of La Union Quinindé. It is a sole proprietorship owned by Eng. Corina Garcia Rosa Garcia, who so far has addressed the company empirically. According to the analysis that had both internal and external, it was found that the areas requiring improvement are: administrative, financial, operational and marketing; because the company lacks advertising, machinery, accounting software and systems management of human talent. The investment required for the proposal to improve the company both in fixed assets, expenses and working capital improvement is USD 90,348.20 dollars. Investment that established by equity capital of the company. The recovery time of the initial investment is 3.46 years, since flows for the proposed improvement in each of the years are positive and allow recovering at this time. The feasibility and viability for the proposed improvement to the company guarantees the execution, because the results of the five-year projections with economic and financial indicators: Net Present Value (NPV) USD 167,398.18; internal rate of return (IRR) 78.27%, generate profitability and productivity of the same.